2015
DOI: 10.1007/978-3-319-14283-8_8
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptations of the Foraminifera and Ostracoda to Fresh Water Colonisation

Abstract: In marine environments Ostracoda and Foraminifera have been very successful invaders. During the Phanerozoic they colonised the majority of shallow, marginal to deep water, fully marine habitats. Both groups had developed physiological adaptations which pre-adapted them to the invasion of new marine habitats. They adopted a broad range of feeding strategies and reproduction modes. The production of resting stages and brood care may also have contributed to them being efficient invaders. They are also both high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…A number of papers discuss the relationship between foraminiferal distribution within lithological successions and their response to their environmental changes (Atkinson, 1971;Murray, 1973Murray, , 1991Murray, , 2006Boltovskoy, 1963;Boltovskoy et al, 1991;Haynes, 1981;Iglikowska and Pawlowska, 2015). Even then, some foraminiferal assemblage changes as well as some specific morphological changes recorded in the fossil material are very difficult to interpret and are not always thoroughly discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers discuss the relationship between foraminiferal distribution within lithological successions and their response to their environmental changes (Atkinson, 1971;Murray, 1973Murray, , 1991Murray, , 2006Boltovskoy, 1963;Boltovskoy et al, 1991;Haynes, 1981;Iglikowska and Pawlowska, 2015). Even then, some foraminiferal assemblage changes as well as some specific morphological changes recorded in the fossil material are very difficult to interpret and are not always thoroughly discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Murray, 1963Murray, , 1973Brasier, 1982;Corliss and Fois, 1990;Boltovskoy et al, 1991;Yanko et al, 1994Yanko et al, , 1998Polovodova and Schönfeld, 2008;Buosi et al, 2010;Mellis and Covelli, 2013;Iglikowska and Pawlowska, 2015). Recent studies based on molecular data show significant variability within distinct molecular groups of foraminifera (Pawlowski and Holzman, 2002;Pawlowski et al, 2003;Longet and Pawlowski, 2007) and prove that two different morphotypes can correspond to the same species in spite of their morphological differences (Pillet et al, 2012(Pillet et al, , 2013.…”
Section: Introductionmentioning
confidence: 98%
“…reduced oxygenation of the near-bottom water layer and pore water and/ or reduced salinity, for calcareous forms to exist (e.g. Iglikowska & Pawłowska 2015). Leckie and Olson (2003) found a marked increase in the abundance of calcareous taxa to accompany the transition from brackish marginal habitats to open neritic conditions.…”
Section: C/a Ratiomentioning
confidence: 99%
“…It is well documented that stygobionts (i.e., taxa occurring exclusively in groundwater during their entire life cycle) can have a double origin (Coineau and Boutin 1992): limnicoid stygobionts derive from epigean freshwater ancestors, while thalassoid stygobionts derive directly from marine ancestors. In the last case, pre-adapted marine species (Iglikowska and Pawłowska 2015), living in the interstitial or in fissured rocky habitats, could have crossed the salinity boundary via an intermediate mixo-to oligohaline coastal zone, and eventually have migrated in inland groundwaters (Boutin and Coineau 1990;Noteboom 1991). It has been suggested that between 9 and 12 independent invasions of freshwaters by marine ostracods have occurred, the first possibly in the early Carboniferous (Iglikowska 2014;Iglikowska and Pawłowska 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last case, pre-adapted marine species (Iglikowska and Pawłowska 2015), living in the interstitial or in fissured rocky habitats, could have crossed the salinity boundary via an intermediate mixo-to oligohaline coastal zone, and eventually have migrated in inland groundwaters (Boutin and Coineau 1990;Noteboom 1991). It has been suggested that between 9 and 12 independent invasions of freshwaters by marine ostracods have occurred, the first possibly in the early Carboniferous (Iglikowska 2014;Iglikowska and Pawłowska 2015).…”
Section: Introductionmentioning
confidence: 99%